Bilateral Three Headed Biceps Brachii Muscle - Singh, Poonam; Tandon, Aseem; Bhatnagar, Rajan; Pokhrel, Rishi (Medical Journal of Shree Birendra Hospital, 2015)
During routine human cadaveric dissection for the purpose of teaching learning of medical undergraduates inour department, third head of the biceps brachii muscle was found bilaterally in a 67 years old male cadaver. Bilaterally symmetrical third head was found with ß eshy proximal attachment on humerus between the insertionof the coracobrachialis and the upper part of the origin of the brachialis. This supernumerary head was deep tothe other two heads of biceps and was inserted into the bicipital aponeurosis. A branch of musculocutaneousnerve could be traced upto the third head. Long and short heads of biceps were of usual anatomy. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12931